Late screw perforation of external iliac artery following acetabular revision. A simple solution for a rare complication - André Sá Rodrigues; Joana Freitas; Isabel Pinto; Sérgio Sampaio; Rui Pinto (Revista Brasileira de Ortopedia)
ABSTRACT Vascular lesions, although quite rare, are one of the most devastating complications in the context of a hip prosthesis. Therefore, the correct diagnosis is crucial to prevent irreversible damage to the patient. The authors present the case of a 70-year-old Caucasian woman with an ischemic lower limb as consequence of a late perforation of external iliac artery due to an acetabular screw. The issue was resolved by simply cutting part of the screw, avoiding other surgical options that would be much more aggressive for the patient. Careful clinical evaluation allowed for a correct diagnosis and a timely creative treatment, preventing further consequences to the patient.